FINANCIAL STABILITY AND DIRECTIONS OF ITS STRENGTHENING: THE CASE OF UKRAINE IN CONDITIONS OF WAR - VOZNYAK, Halyna; DMYTRYK, Olga (Scientific journal «World of Finance», 2022)
Introduction. The large-scale Russian invasion of Ukraine has not only caused catastrophic destruction of residential, industrial, and transport infrastructure but also generated the changes and reinforced the threats to the financial stability of Ukraine. From this point of view, the issues of detecting the risks and threats to financial stability in Ukraine in conditions of war and military law require particular attention. It makes the issue of developing new approaches to the implementation of the adaptive budget, tax, and debt policy and the accomplishment of quick, systemic, and efficient policy measures in new conditions quite relevant.The purpose of the article is to determine the risks and threats to the financial stability of Ukraine in conditions of war and substantiate the recommendations for its reinforcement.Results. The major trends in the functioning of the public finance sector and domestic banking system of Ukraine in conditions of the Russian-Ukrainian war are detected. The risks and threats affecting financial stability in Ukraine are determined. The public programs to support internally displaced people are analyzed. The possibilities of strengthening financial imbalances caused by military aggression are emphasized. The innovations introduced by the Government in tax and customs domains with the view to “mitigate” shocks in the economy of Ukraine are analyzed. Their consequences for the country are substantiated. The article shows that the reduced tax revenues during the two months of the war in Ukraine are partially caused by simplified budget procedures. The directions of strengthening the financial stability in terms of budget savings and increasing the international macro-financial assistance following the principles of targeted spending and management in full compliance with the EU standards and procedures are outlined. The reasonability of zoning the areas depending on the risk of financial-economic resilience violation is emphasized.Conclusions. According to the results of the study, the expediency of zoning territories taking into account the risk of financial and economic sustainability is emphasized, with the following types being distinguished: a) territorial communities in the rear with low risks for financial and economic sustainability, but a significant number of internally displaced persons; b) territorial communities with increased potential risks for disruption of financial and economic stability; c) territorial communities in the combat zone and frontline territories; d) temporarily occupied territorial communities.